CONTENT ANALYSIS OF CIGARETTE PACKS IN INDONESIA: REGULATORY NON- COMPLIANCE AND PRODUCT PROMOTION ADVANTAGE - Bigwanto, Mouhamad; Soerojo, Widyastuti (YCAB Publisher & IAKMI SULTRA, 2020)
Background: A cigarette pack is the most intimate property and frequently seen by smokers every time they want to start smoking. It gives tobacco industry the opportunity to scrutinize every single space including the inside part of the pack to promote tobacco product and it is often called a mini billboard.Objective: To analyze possible violations if any against the existing regulations on packaging and labelling and to uncover packaging design and types of promotional elements on cigarette packs. Methods: A purposive sample based on the assessment and discussion with the representatives of National Agency of Drug and Food Control that generated a total of 42 cigarette packs representing 18 sample from Jakarta, 5 most popular brands, 18 special edition packs, and 1 illegal cigarettes. The observation units, variables and observable signs that covered the materials, size, content of the entire pack including the cigarettes stick were set by Southeast Asia Tobacco Control Alliance and analyzed against the existing regulation.Results: There were two brands produced in 2019 that did not comply with the latest sets of Pictorial Health Warning. About 40.5% of sample (n=17) did not include information on production dates on the pack as mandated by Government Regulation Number 109/2012. The back panels of the top of pictorial health warning in all machine-made cigarettes were partially bunged up by excise tax stamps with exception of hand-rolled clove cigarettes. The tobacco industry took the advantage of the cigarette packs' violations for product promotion, among others providing information on filter technology, promoting the upcoming tobacco-sponsored events, relating the product with imported goods by mentioning the country of brand origin, and using the flip lid of the pack to promote the brand name reputation. A total of 83.3% (n=35) samples gives additional products description such as bold, mild, lights, super, and special.Conclusion: The tobacco industry uses the ample spaces on both outer and inner panels of cigarette packs to promote their products, no single corners are left empty. The study confirmed violations of the regulation for product promotion.